Strengthening Competitiveness Strategy Of PT RAR In Facing Challenges Of Financial Literacy, Digital Transformation, And Competition In The General Insurance Industry In Indonesia - Budhialon, Poltak Robert; Azhari, Ihsan; Johanes RMP, Timbo; Rakhman, Sitti (Jurnal Multidisiplin Sahombu, 2025)
This study analyzes the main challenges faced by PT RAR in the general insurance industry in Indonesia, namely low public financial literacy, suboptimal digital transformation, and intense market competition. Using a descriptive qualitative approach, the study employs Prospect Theory and Porter’s Five Forces to evaluate the company’s issues and strategies. The findings indicate that low financial literacy hinders market penetration, limited digital transformation reduces operational efficiency, and competition necessitates product differentiation. Recommendations include financial literacy campaigns, digital technology optimization, and product innovation based on local needs. These strategies are expected to enhance PT RAR's competitiveness and growth in the Indonesian insurance market.